MODEL LASSWELL DALAM KOMUNIKASI PEMBANGUNAN KAWASAN WISATA BENGKULU - Linda Astuti; Khairil Buldani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
As a consequence of the optimization resources area policy, tourism was becoming one of the favored sectors. Development of the tourism sector could run well with good communication between the Government and society, so communication was considered important in the development process. Therefore, it was necessary to develop a communication strategy so that messages could be received well. The purpose of this study was to determine the communication strategy development undertaken by the Department of Culture and Tourism of Bengkulu province in tourism development by using analytical tools Lasswel components. Research results showed that the Department of Culture and Tourism has been communicated by applying the Lasswell model.